2010
DOI: 10.1186/1749-8090-5-117
|View full text |Cite
|
Sign up to set email alerts
|

Bone healing after median sternotomy: A comparison of two hemostatic devices

Abstract: BackgroundBone wax is traditionally used as part of surgical procedures to prevent bleeding from exposed spongy bone. It is an effective hemostatic device which creates a physical barrier. Unfortunately it interferes with subsequent bone healing and increases the risk of infection in experimental studies. Recently, a water-soluble, synthetic, hemostatic compound (Ostene®) was introduced to serve the same purpose as bone wax without hampering bone healing. This study aims to compare sternal healing after applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
2
37
0
1
Order By: Relevance
“…Unlike other specialties, in which radiographic standards have been developed to assess bone healing, no standards exist to assess bony healing after a sternotomy [16][17][18][19]. The methods developed for other orthopaedic specialties have clinical implications, and may be used to determine when patients may return to normal activities or when hardware may be removed.…”
Section: Commentmentioning
confidence: 99%
“…Unlike other specialties, in which radiographic standards have been developed to assess bone healing, no standards exist to assess bony healing after a sternotomy [16][17][18][19]. The methods developed for other orthopaedic specialties have clinical implications, and may be used to determine when patients may return to normal activities or when hardware may be removed.…”
Section: Commentmentioning
confidence: 99%
“…Zhang et al (2012) suggested that an injectable nanohydroxyapatite/chitosan scaffold was a potential candidate material for regeneration of bone loss. Vestergaard et al (2010) indicated that the use of Ostene instead of bone wax could contribute to a reduction in the incidence of sternal dehiscence and chronic inflammation. Cho et al (2012) suggested the application of a thrombinsoaked, absorbable gelatin compressed sponge at the end of multilevel posterior cervical spinal surgery significantly decreased post-operative drain output.…”
Section: Introductionmentioning
confidence: 98%
“…Due to its immediacy and effectiveness of hemostasis, ease of use and low cost, it is still widely used in surgical procedures. Although it is an effective hemostatic device, which creates a physical barrier to stop bleeding, bone wax remains at the implantation site indefinitely and influences subsequent bone growth (Vestergaard et al 2010). Moreover, it has a potential risk of infection in clinical applications (Gibbs et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…16,22,30 Likewise, application of bone wax to the exposed cut bone helps with hemostasis and may reduce the rate of bone reaccumulation. 31,32 This is the first study to describe the use of intraoperative navigation for the resection of anterior cervical osteophytes, which has multiple advantages. Following provisional resection, intraoperative 3-D scanning can determine the amount and location of remaining osteophytes, whereas navigated probes and burs allow for real-time guidance during final bony resection.…”
Section: Discussionmentioning
confidence: 99%